2006
DOI: 10.1016/j.chemosphere.2005.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phosphate on the adsorption of Cu and Cd on natural hematite

Abstract: Interactions between anions and cations are important to understand the chemical processes of pollutants in environment. In this study, batch experiments were carried out to investigate the simultaneous adsorption of Cu and Cd on hematite as affected by phosphate. Phosphate pretreatment suppressed the maximum adsorption of Cu and Cd on hematite and moved the adsorption pH edges to a higher pH range. Phosphate application time had a marked impact on Cu and Cd adsorption and longer contact time resulted in more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 28 publications
2
29
0
Order By: Relevance
“…This may indicate the mechanism of inner-sphere sorption, which occurs in a plane that is closer to the surface compared to that where the background electrolyte ions stay, and is generally not affected by ionic strength [29]. Innersphere sorption mechanism was also reported in the research of phosphate and Cd adsorption on hemitate [30,31].…”
Section: Effects Of Ph and Ionic Strengthmentioning
confidence: 81%
“…This may indicate the mechanism of inner-sphere sorption, which occurs in a plane that is closer to the surface compared to that where the background electrolyte ions stay, and is generally not affected by ionic strength [29]. Innersphere sorption mechanism was also reported in the research of phosphate and Cd adsorption on hemitate [30,31].…”
Section: Effects Of Ph and Ionic Strengthmentioning
confidence: 81%
“…The phosphate reduced Pb adsorption on montmorillonite, these attributed to the adsorbed phosphate which partially prevented the added Pb penetrating into the interlayer space of montmorillonite, thus, the phosphate can decrease the interlayer of adsorption for Pb [36]. On another hand, phosphate can also lower surface electrostatic potential near the solid surface and therefore, enhance the Pb uptake through outer layer complexes [36]. However, this description does not mean that the adsorption of Pb only occurs as inner-sphere complexes.…”
Section: Lead Sorptionmentioning
confidence: 99%
“…On the other hand, oxyanions and heavy-metal cations often co-exist in the environment, and their co-adsorption behaviors of the two species on geosorbents therefore have received great concerns as well (Diaz-Barrientos et al, 1990;Swedlund et al, 2003;Li et al, 2006). Prior studies revealed that the adsorption of heavymetal cations (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, most of the co-adsorption studies focused on goethite (α-FeOOH) (Wang and Xing, 2002;Kanematsu et al, 2013), hematite (α-Fe 2 O 3 ) (Li et al, 2006), and clay minerals (Zhu et al, 2014), while Fh received less concern. The limited studies showed that oxyanions and heavy metal cations generally can be synergistically adsorbed on Fh (Swedlund et al, 2003;Song et al, 2008;Tiberg et al, 2013;Carabante et al, 2012).…”
Section: Introductionmentioning
confidence: 99%